The Retail Payment Costs and Savings in Albania - World Bank Group (World Bank, Washington, DC, 2018)
This report is based on a study of the costs and savings of retail payments in Albania using a methodology (A Practical Guide for Measuring Retail Payment Costs) developed by the World Bank’s Payment Systems Development Group, part of the Financial Inclusion, Infrastructure, and Access at the Finance, Competitiveness, and Innovation Global Practice. By applying this methodology to Albania, the study aims to establish a sound economic baseline for the national retail payments system in terms of costs of different payment instruments to better guide system development and enable high-impact changes. Moreover, the methodology allows for the development of substitution scenarios (from more costly to less costly retail payment instrument) and the resulting cost savings. It is designed based on four main principles: applicability, comparability, efficiency, and standardization and can be adapted to country-specific circumstances without losing its comparative nature, across time and across countries.